Synthesis of uniform poly(d, l‐lactide) and poly(d, l‐lactide‐co‐glycolide) microspheres using a microfluidic chip for comparison. Issue 2 (February 2014) - Yang, Chih‐Hui; Huang, Keng‐Shiang; Grumezescu, Alexandru Mihai; Wang, Chih‐Yu; Tzeng, Shian‐Chiuan; Chen, Szu‐Yu; Lin, Yu‐Hsin; Lin, Yung‐Sheng; Foret, Franta; Kutter, Jörg P.
<x xml:space="preserve">Abstract</x> Electrophoresis 2014, 35, 316‐322. DOI: 10.1002/elps.201300185 This study used a phenol formaldehyde resin‐based microfluidic chip to synthesize uniform poly(D, L‐lactide) and poly(D, L‐lactide‐co‐glycolide) microspheres for comparison. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>